Evaluation of post infant hepatitis B vaccination among healthy vaccinees and molecular detection of occult hepatitis B among healthy volunteers - Shuaibu, Hudu Abdullahi (2014)
Hepatitis B virus is the commonest chronic viral pathogen affecting about 2 billion people worldwide. Of these, 378 million are chronic carriers. In Malaysia, 2.4 million people have been estimated to be hepatitis B carriers and this population continues to be a potential source of infection, to tackle these more than 100 countries adopted National policy on infant hepatitis B vaccination including Malaysia and it has been shown to effectively control the diseases even in endemic areas. The production of hepatitis B surface antibodies (anti-HBs) has been reported to confer long-term protective immunity; these antibodies are produced in response to vaccination or exposure to HBV infection. Hepatitis B core antibody (anti-HBc) on the other hand, are detected in almost all individuals that have been previously exposed to the virus.The success of childhood vaccination against hepatitis B relies mainly on persistence of immunity to adulthood, however, mutation in the surface antigen is becoming a global challenge because these mutants seldom respond to the currently available vaccine and escaped been detected by current serological screening methods. At the moment, there is lack of information regarding the assessment of HBV vaccination in Malaysia; moreover, evidences are scanty regarding occult hepatitis B infection among Blood donors and vaccinees. It is against this background that the present study was carried out with the following objectives; (i) to evaluate the persistence of immunity following childhood hepatitis B vaccination among vaccinated undergraduate Student. (ii) to investigate the prevalence of isolated hepatitis B core antibody among vaccinated undergraduate Students cohort (iii) to detect occult hepatitis B viral infection among Blood donors and undergraduate students using serological and molecular methods and (iv) to perform molecular characterization of occult hepatitis B virus using bioinformatics tools.This study involved two population, these are undergraduate students vaccinated at infant and blood donors. Objective one and two are related to the former while objectives three and four are related to the later. Sample size was calculated using sample size formula by Daniel, 1999 for estimating minimum sample size in cross-sectional study. Minimum sample size for each of the study population was found to be 379 and 153 for undergraduate vaccines and donors respectively. However, there were 402 undergraduate students that were eligible for this study and all were included while the sample size of the blood donor was also increase to 1000 to increase the precision of the sample. Serum samples from both vaccinated undergraduate students and the blood donors were tested for HBsAg and anti-HBc while only the undergraduate vaccines were tested for anti-HBs pre and post vaccine booster using commercially available Enzyme-linked Immunosorbent Assay (ELISA). A booster dose of 20μg recombinant hepatitis B vaccine (Euvax B, Sanofi Aventis, Malaysia) was administered to individuals with negative anti-HBs (<10 IU/L) and their anti-HBs status was evaluated one month after the booster dose. To further elucidate the genetic characteristic of hepatitis B variant, all anti-HBc positive and HBsAg negative samples from both undergraduate vaccines and blood donors were selected for hepatitis B surface mutation analysis. The DNA was extracted from all anti-HBc positive samples and Nested PCR was done using two set of primers targeting S-gene region of hepatitis B envelope proteins. Samples with positive HBV DNA were purified, sequenced and subjected to bioinformatics analyses. The results showed that none of the samples were found to be HBsAg positive, while 5.5% were found to be anti-HBc positive. For the anti-HBs of vaccinated undergraduate student the results showed that 83.9% were anti-HBs positive ( > 10 IU/L) pre booster dose, majority (67.9% ) of which received three doses of the vaccine and 94% anamnestic response post booster dose with only nine non-responders and were given two doses of the vaccine to receive the third dose in six month time. All the 55 anti-HBc positive samples were found to be HBV DNA positive by nested PCR. Sequence analysis of the amplified product revealed a 99% identity to HBV with most of the local isolates having close phylogenetic relationship with HBV isolate 14 (JX869999) from Panama. This isolate belongs to genotype B, serotype adw2 and was isolated from plasma of Chinese population living in Latin region of Panama. This study therefore, reveals the persistence of immunity for an average of 21 years post primary vaccination with recombinant hepatitis B vaccine and 67.9% of the vaccinees with protective anti-HBs (>10 IU/L) received three doses of the vaccine with a significant association between number of doses receive and persistence of immunity (P<0.05) which is similar to a recent finding in UK. Thus, the presence of immune memory post-infant vaccination has been confirmed in this study, as well as other related studies with anamnestic response, indicating persistence of memory beyond the duration of circulating antibodies. The rate of anti-HBc-positive subjects among the vaccinated undergraduate students was found to be 5% with isolated anti-HBc in 0.9% of the vaccinees. All the four isolated anti-HBc response to a single dose of recombinant hepatitis B vaccine which suggests primary infection with mutant variant of HBV. Hepatitis B viral DNA was detected from all the 55 anti-HBc positive, HBsAg negative serum using nested PCR, which is in line with previous studies that demonstrated similar finding in serum, mononuclear cells and liver samples. Based on sequence and phylogenetic relationship of our HBV isolates and reference isolates from other parts of the world, we found that all our isolates belong to genotype B. Another interesting finding from this study is the occurrence of occult hepatitis in 3 % and 2 % of the blood donors and undergraduate students respectively. All hepatitis B core antibodies positive were found to be HBV DNA positive thus, indicating the reliability of hepatitis B core antibodies in screening for occult hepatitis B infection, especially in low endemic regions while nucleic acid amplification testing (NAT) is the recommended screening test in high endemic regions. Bioinformatics analysis revealed that mutation at position 16 of the amino acid is common to all the 55 isolates with substitution of Glutamine (Q) with Lysine (K) in 53 of the isolate, while the remaining 2 isolates have Arginine and stop codon respectively. A total of 105 amino acid mutations, were found in all the 55 isolates. In conclusion, the evidence presented in this study, reveals persistence of both humoral and cellular immunity for an average of 21 years after infant vaccination and presence of isolated anti-HBc in vaccines which response to a single dose of recombinant hepatitis B vaccine suggesting primary infection with mutant variant of HBV despite the presence of cellular immunity against the none mutant hepatitis B virus. The presence of HBV DNA in all the anti-HBc positive samples may suggest the reliability of the use of hepatitis B core antibodies in screening for occult hepatitis B infection. All the 55 sequences in this study belong to genotype B and have various mutations in different regions of the S gene with the most common mutations found in this study are substitution of Glutamine at position 16 with lysine resulting in nonfunctional hepatitis B surface antigen therefore; mutation outside the a determinant region might play a role in hepatitis B surface antigen detection failure.